The Composite of ZrO2-TiO2 Produced from Local Zircon Sand Used as A Photocatalyst for The Degradation of Methylene Blue in A Single Batik Dye Wastewater - Ita Permadani; Dhini A. Phasa; Andini W. Pratiwi; Fitria Rahmawati (Bulletin of Chemical Reaction Engineering & Catalysis, 2016)
In this research, a composite of ZrO2-TiO2 was used as a photocatalyst in the degradation of dye wastewater. The dye waste water is a single Methylene Blue, MB, wastewater from Batik industry. Meanwhile, the ZrO2 was prepared from zircon sand founded from Bangka Island, Indonesia. The composite was prepared at various weight ratio and heat treated at 500 oC. The result shows that the purity of ZrO2 from zircon sand is only 66.46 %. However, the addition of ZrO2 into TiO2 able to increase the photocatalytic activity proven by 88.75 % degradation of MB at a ZrO2-TiO2 weight ratio of 1:1. The result is higher than the degradation with anatase TiO2; that is only 62.67 %. The kinetics study found that the photocatalytic degradation of MB with single TiO2 has the rate constant of 1.85x10-2 minutes-1. Meanwhile, the rate constant of the MB degradation with the composite ZrO2-TiO2 is 16.73x10-2 minutes-1.